Kendala implementasi P5 dengan tema bhinneka tunggal ika di sekolah dasar - Nisa Bastrian; Sri Marmoah; Fadhil Purnama Adi (Didaktika Dwija Indria, 2024)
This research was conducted to examine the obstacles to implementing P5 with the topic Bhinneka Tunggal Ika at SDN Bumi 1 No. 67 Surakarta starting from the planning stage, implementation, to assessment and efforts made to overcome it. This research uses a qualitative descriptive method approach. The obstacles encountered in the implementation of P5 are due to internal factors and external factors. The obstacles caused by internal factors are the absence of training regarding P5 for teachers, P5 is not well documented due to lack of teacher understanding, and differences in perception between teachers and school principals. Meanwhile, obstacles are caused by external factors such as limited learning media, the lack of role of teachers and school principals in establishing collaboration, and the lack of involvement of committees and supervisors. The solution to overcome these obstacles are to encourage the strengthening of teacher capacity through training to be able to implement P5 in accordance with the guidelines, to equalize perceptions and build communication between teachers and the school principals, to work with the parents of pupils in providing adequate learning media and to optimize the role of the head, teacher, committee, and supervisor to support a collaborative school ecosystem.